MAKING A PROTECTIVE ROOF FOR PORTABLE COMPOST FERTILIZER MEDIA SYSTEMS FOR GARDENS IN BUKIT TUNGGAL VILLAGE, PALANGKA RAYA CITY - Revianti Coenraad; Wiratno Y Sigin; Trissan, Whendy; Topan Eka Putra; Frans Putra Ganesa; Sri Wahyuni (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
Agriculture is the economic backbone and source of life for many communities in Indonesia, including the City of Palangkaraya. The Sumber Makmur Farmers Group is a clear example of an agricultural community that strives to increase crop production and manage organic waste sustainably. However, they often face obstacles in producing quality compost due to external weather influences. Through this community service, we can also increase awareness of the importance of sustainable and environmentally friendly agricultural practices. The Sumber Makmur Farmers Group can be an example for other communities in implementing simple but effective technology to increase agricultural productivity in a sustainable manner. Thus, the activity of making a protective roof for portable compost fertilizer systems is not only a technical contribution to local agriculture, but is also a real effort to advance community welfare and maintain environmental sustainability in Palangka Raya City.